Factors Influencing E-Banking Adoption in Rural Communities: A Case Study of Batang Kuis - Prayogo, Irgi; Sugianto, Sugianto; bi rahmani, Nur ahmadi (Universitas Diponegoro, 2025)
Banking adoption in rural communities, specifically in the Batang Kuis area. The results of data analysis indicate that perceived profit and security are the dominant factors encouraging e-banking adoption among the rural community in Batang Kuis. This research contributes to the existing literature by aligning with Utility Theory and TAM Theory , which posits that perceived benefits and actual benefits are key drivers of individual technology adoption. Based on these findings, this study recommends improving security measures, enhancing financial literacy through education programs, and improving infrastructure in rural areas to foster greater e-banking adoption. This necessitates collaboration between financial institutions and government agencies. However, this research has limitations, including a limited sample size and a restricted scope of variables. Future research could expand the sample and incorporate a wider range of variables for a more comprehensive understanding of e-banking adoption in rural settings.